A Causal Model of Servant Leadership of Administrators and Teacher Skills in the 21st Century with Work Engagement as Mediator, Affecting Job Performance of Nursing Instructors in Nursing Education Institutions, the Office of the Higher Education Commission. - Tungtrijuk, Napatip; Sanswang, Sudarat; Buasuwan, Prompilai; Lupanachokdee, Warunee (Journal of Research in Nursing-Midwifery and Health Sciences, 2019)
This research aimed to analyze a causal model of job performance of nursing instructors in nursing education institutions, the office of the higher education commission. The research samples were 273 nursing instructors in 15 nursing education institutions, the office of the higher education commission, selected by stratified random sampling technique. The research instrument was a questionnaire with five levels rating scale. The IOC was between .60-1.00 and the reliability was .97. Data were analyzed descriptive statistics and Structural Equation Modeling. The research findings were as follows: 1) Servant leadership of administrator had not a direct on the job performance of nursing instructors. 2) Teacher skills in the 21st century and work engagement had a direct on the job performance of nursing instructors. 3) The relationship of servant leadership of administrator was not mediated by work engagement with the job performance of nursing instructors. 4) The relationship of teacher skills in the 21st century was mediated by work engagement with the job performance of nursing instructors. 5) A causal model of job performance of nursing instructors is in accordance with the empirical data. (x^2 = 121.26 P-value = .06 df = 98 RMSEA = .03 GFI = .95 AGFI = .92)